Developing an assessment framework of multidimensional scientific competencies - Sasima Intasoi; Putcharee Junpeng; Keow Ngang Tang; Jatuphum Ketchatturat; Yidan Zhang; Mark Wilson (Institute of Advanced Engineering and Science, 2020)
The study aimed to develop and validate an assessment framework of multidimensional scientific competencies for seventh-grade students in the northeastern region of Thailand. A total of 289 samples with three different scientific competency levels were randomly selected to participate as testtakers. The design-based research encompassing four phases of the construct modelling approach, namely construct maps, item design, outcome space, and Wright map. Multidimensional Random Coefficient Multinomial Logit model was employed to examine the quality of the created assessment framework of multidimensional scientific competencies. The results showed that scientific competence is comprised of three dimensions, namely explain phenomena scientifically, evaluate and design scientific inquiry, and interpret data and evidence scientifically. Each dimension can be further categorized into four levels. The assessment framework consists of 16 items. The results revealed that there is validity evidence regarding internal structure based on the comparison of the model fit and Wright map. Moreover, results also indicated that the reliability evidence and item fit are compliance with the quality of the assessment framework as revealed in the analysis of standard error of measurement and infit and outfit of the items. It can be concluded that the assessment framework is currently prevalent to assess the scientific competencies of seventh-grade students.